2022
DOI: 10.1093/cid/ciac103
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Coronavirus Disease 2019 (COVID-19) Vaccine Responses Across a Broad Spectrum of Immunocompromising Conditions: the COVID-19 Vaccination in the Immunocompromised Study (COVICS)

Abstract: Background We studied humoral responses after COVID-19 vaccination across varying causes of immunodeficiency. Methods Prospective study of fully-vaccinated immunocompromised adults (solid organ transplant (SOT), hematologic malignancy, solid cancers, autoimmune conditions, HIV infection) versus non-immunocompromised healthcare-workers (HCW). The primary outcome was the proportion with a reactive test (seropositive) for IgG to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 29 publications
7
77
1
Order By: Relevance
“…breakthrough) SARS-CoV-2 infection. 4-9 Our prior study showed a 28% increased risk for breakthrough SARS-CoV-2 infection in PWH compared to people without HIV (PWoH), although breakthrough cumulative incidence was low (PWH=3.1%, PWoH=2.5%), consistent with findings among people with other immunosuppressive conditions. 4,5,9 Data on breakthrough COVID-19 illness, particularly severe illness requiring hospitalization, in PWH remain sparse 10,11…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…breakthrough) SARS-CoV-2 infection. 4-9 Our prior study showed a 28% increased risk for breakthrough SARS-CoV-2 infection in PWH compared to people without HIV (PWoH), although breakthrough cumulative incidence was low (PWH=3.1%, PWoH=2.5%), consistent with findings among people with other immunosuppressive conditions. 4,5,9 Data on breakthrough COVID-19 illness, particularly severe illness requiring hospitalization, in PWH remain sparse 10,11…”
Section: Introductionsupporting
confidence: 62%
“…[4][5][6][7][8][9] Our prior study showed a 28% increased risk for breakthrough SARS-CoV-2 infection in PWH compared to people without HIV (PWoH), although breakthrough cumulative incidence was low (PWH=3.1%, PWoH=2.5%), consistent with findings among people with other immunosuppressive conditions. 4,5,9 Data on breakthrough COVID-19 illness, particularly severe illness requiring hospitalization, in PWH remain sparse 10,11 Studies on the severity of breakthrough COVID-19 illness by HIV status are equivocal, some finding comparable severity, [12][13][14][15] while others have reported a higher risk of developing severe illness and worse outcomes, including death, for PWH compared to PWoH. [16][17][18][19] Immune dysfunction is believed to increase severe COVID-19 illness risk in PWH, with lower CD4 counts and detectable HIV viral loads associated with worse outcomes.…”
Section: Introductionsupporting
confidence: 57%
“…While antiretroviral therapy can reverse HIV-induced immune dysfunction to a large extent [13-16], persistent HIV-related immunopathology can nevertheless blunt vaccine responses [17-19], prompting initial concern that PLWH may respond sub-optimally to COVID-19 immunization. Data from clinical trials [20, 21] and real-world studies however [22-27], including from our group [28], described strong initial immune responses to two-dose COVID-19 vaccination in PLWH with controlled HIV loads on therapy and preserved CD4+ T-cell counts [20-24, 28], though weaker responses have been observed in PLWH who are not receiving therapy or who have CD4+ T-cell counts <200 cells/mm 3 [22, 25-27].…”
Section: Introductionmentioning
confidence: 99%
“…SARS‐CoV‐2 infection causes substantial morbidity and mortality in solid organ transplant recipients (SOTRs). 1 , 2 , 3 , 4 Vaccination holds promise to reduce COVID‐19 severity in SOTRs, but a significant subset does not develop antibody response after two‐ and three‐dose mRNA vaccine series, 5 , 6 , 7 , 8 which likely contributes to higher rates of COVID‐19 breakthrough after vaccination. 4 Heterologous vaccination (“mixing platforms”) is one potential mode to augment aspects of immune sero‐response, 9 , 10 , 11 , 12 but data are limited in SOTRs.…”
Section: Introductionmentioning
confidence: 99%